Characterizing changes in abdominal aortic aneurysms using principal wall strain ultrasound elastography - Kedwai, Baqir J.; Zottola, Zachary R.; Lehane, Daniel J.; Geiger, Joshua T.; Stoner, Micheal C.; Richards, Michael S.; Mix, Doran S. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAortic principal wall strain is a biomechanical parameter correlated with aneurysm growth rate that affects abdominal aortic aneurysm (AAA) stability. Characterize changes in pressure-normalized maximum mean aortic principal wall strain (ερ+¯/PP) using ultrasound elastography (USE).MethodsAxial ultrasound images of patient AAAs were collected at two consecutive clinic visits. The ερ+¯/PP for each image was calculated using a novel finite element mesh technique. The cohort was separated by index ερ+¯/PP terciles, and the rate of strain change, growth, intervention, and rupture were compared.Results31 patients with a median age of 72.0 [65.0, 77.5] at index visits were included, with follow-up imaging taken at an average interval of 6.2 [6.0, 8.3] months. For the whole cohort, maximum ερ+¯/PP decreased from 2.1 [1.1, 2.7] %/mmHg to 1.9 [1.3, 2.6] %/mmHg (p = 0.08), and maximum AAA diameter increased from a median of 4.3 [4.0, 4.7] cm to 4.4 [4.1, 4.9] cm (p = 0.04). The “high-strain” tercile was associated with a strain reduction of −1.3 [−2.5, −1.1] %/mmHg between index and follow-up imaging, as compared to the “low-strain” (−0.1 [−0.6, 0.5] %/mmHg, p < 0.01) and “intermediate-strain” (−0.4 [−0.5, −0.3] %/mmHg, p = 0.04) terciles. There was no difference in the rate of AAA growth, intervention, or rupture between terciles.DiscussionThe present findings indicate that ερ+¯/PP at baseline predicts the degree and direction of ερ+¯/PP change in AAAs over time. These findings offer insight into the natural history of AAA tissue mechanics and demonstrate the potential for a novel ultrasound technique to quantify biomechanical changes in the aortic wall. These findings may aid in the development of patient-specific risk stratification tools informed by biomechanical data in addition to conventional size-based criteria.